Evaluation of two cationic dyes removal from aqueous environments using CNT/MgO/CuFe2O4 magnetic composite powder: A comparative study. Issue 2 (April 2021) - Foroutan, Rauf; Peighambardoust, Seyed Jamaleddin; Esvandi, Zahra; Khatooni, Hamzeh; Ramavandi, Bahman
Graphical abstract: A schematic for CNT/MgO/CuFe2 O4 production. Highlights: A CNT/MgO/CuFe2 O4 magnetic composite was produced by the co-precipitation method. The composite was used to remove cationic dyes (methyl violet and Nile blue). The mesoporous and crystalline composite had a BET surface area of 127.58 m 2 /g. The maximum capacity of cationic dyes adsorption was determined > 35 mg/g. A sample of real textile wastewater was treated using composite (COD removal: 74 %). Abstract: In the present study, the elimination of methyl violet dye (MVD) and Nile blue dye (NBD) from water solution using a CNT/MgO/CuFe2 O4 magnetic composite powder produced by co-precipitation was investigated. The BET analysis showed that the generated magnetic composite is a mesoporous material (based on IUPAC classification) and its specific surface area value is 127.58 m 2 /g. Also, the magnetic composite powder had a crystalline structure and a magnetic saturation of 12.137 emu/g. In the adsorption process, the effect of various effective parameters such as working pH, temperature, adsorbent dose, initial concentration of dye solutions, and time was investigated. The maximum capacity of monolayer adsorption for MVD and NBD was determined to be 36.46 mg/g and 35.60 mg/g, respectively. The results showed that the experimental data follow the pseudo-second-order (PSO) model. Based on the intra-particle diffusion (IPD) model, more than one mechanism is involved in the adsorption process. The values of Gibbs free energy parameter were determined negatively for both types of dyes, indicates the adsorption of the desired dyes is spontaneous. The enthalpy values (ΔH°) indicated that the removal of the cationic dye is exothermic and the magnetic composite powder has a good ability to adsorb MVD and NBD from aqueous solution at low temperatures. The magnetic composite powder could be used several times in the adsorption process of MVD and NBD without a significant reduction in the removal efficiency. The results showed that the CNT/MgO/CuFe2 O4 magnetic composite powder can be successfully used in textile wastewater treatment.